Identity, <span>For example, x + x = 2x is </span>true for every value<span> of x.</span>
Answer:
-2
Step-by-step explanation:
The average rate of change on an interval is ...
average rate of change = (amount of change)/(width of interval)
= (-3 -1)/(1 -(-1)) = -4/2 = -2
The average rate of change between (-1, 1) and (1, -3) is -2.
Answer:
Letter a)
Step-by-step explanation:
quizlet
To rewrite it as a single exponent we have to simply add the exponents since we have an equal base.
The answer is 9^7